Unknown Enemy and Psychopathological Responses: A Cross-Sectional Nationwide Study Assessing the Knowledge About COVID-19 - Maciaszek, Julian; Lenart, Marta; Misiak, Błazej; Grzebieluch, Jolanta; Gawłowski, Paweł; Ciułkowicz, Marta; Łuc, Dorota; Szcześniak, Dorota; Rymaszewska, Joanna (Frontiers in Psychiatry, 2021)
There is evidence that a lack of appropriate knowledge regarding global changes might be associated with various psychopathological responses. In this study, we tested the hypothesis that knowledge about COVID-19 correlates with the severity of psychopathological symptoms as measured by standardized questionnaires. The questionnaires were obtained using the Computer Assisted Web Interviews (CAWI) method during the second wave of the COVID-19 pandemic in Poland using the original COVID-19 knowledge questionnaire and the General Health Questionnaire-28 (GHQ-28). A series of bivariate tests and linear regression analyses were performed with a p-value less than 0.05. All analyses were performed in Statistica 13.3. We enrolled 1,002 respondents. The rate of correct answers in the original questionnaire ranged from 44.6% to 84.1%, and the average was 60.1%. 420 participants (42%) met the criterion for the presence of relevant psychopathological symptoms. A significant negative correlation was found between the number of points obtained in the COVID-19 knowledge questionnaire and the GHQ-28 scores, both in relation to the total score and all its subscales. The following factors in the linear regression model were correlated with severity of somatic symptoms: knowledge about the COVID-19 pandemic (B= -.12, P= .000), sex (B= 0.12, P= .000), use of psychiatric or psychological care (B= .20, P <.000) and chronic diseases (B= .09, P= .002). In this study, we observed a negative correlation between the knowledge about the COVID-19 pandemic and the severity of psychopathological symptoms. The results clearly indicate that the complexity of the global problem of the current pandemic is related to the development of psychopathological symptoms. However, longitudinal studies are needed to identify the direction of causality.